Sistem Informasi Pemesanan dan Promosi Pekerjaan Bidang Konstruksi CV Tri Setya Abadi Semarang Berbasis Web - Prastyanto, Dicky Dwi; Putra, Toni Wijanarko Adi; Kuncoro, Arsito Ari (VISA: Journal of Vision and Ideas, 2025)
CV Tri Setya Abadi is a company located in Central Java, precisely in Semarang, which is engaged in construction work, there are various construction models such as Aluminum Kitchen Sets, Aluminum Cupboards, Iron Railings and Balconies, and Stainless Steel Railings and Balconies. CV Tri Setya Abadi only serves consumers who buy directly, namely by coming to the location of CV Tri Setya Abadi therefore consumers who do not visit this company do not get complete information about construction models, prices, and available goods. This ordering technique is less effective where currently it is an online era, therefore the purpose of this study is to create an information system for ordering and promoting work in the construction sector of CV Tri Setya Abadi Semarang based on a website that can make it easier for consumers to buy and get information about construction work. The research method used in this study is the waterfall model. The results of this study using the Laravel framework produce structured project files and with the libraries available in the Laravel framework, researchers can be assisted in their development. In this website there are home, shop, contact us features so that consumers can use it. So with this website it can help consumers as a means of ordering construction work online.